Two new species of Haliclona Grant, 1836 (Haplosclerida: Chalinidae) from Sergipe State, Brazil - Sandes, Joana; Bispo, André; Pinheiro, Ulisses (Zootaxa, 2014)
Haliclona is one of the most species-rich genera among Demospongiae, but with only 11 species recorded for the Brazilian coast. Here we describe two new species of Haliclona collected by trawling at Sergipe State (Northeastern Brazil). Haliclona (Halichoclona) dura sp. nov. is distinguished by the combination of confused choanosome with dense reticulation, oxeas with stepped and mucronate points, color dark brown externally and light beige internally, consistency firm and incompressible. Haliclona (Soestella) brassica sp. nov. is set apart by the combination of a choanosomal skeleton with rounded meshes, strongyles, raphides, color beige and consistency soft.